2021
DOI: 10.3390/antiox10020255
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Compromises Lymphocyte Function in Neonatal Dairy Calves

Abstract: Dairy calves are unable to mount an effective immune response during their first weeks of life, which contributes to increased disease susceptibility during this period. Oxidative stress (OS) diminishes the immune cell capabilities of humans and adult cows, and dairy calves also experience OS during their first month of life. However, the impact that OS may have on neonatal calf immunity remains unexplored. Thus, we aimed to evaluate the impact of OS on newborn calf lymphocyte functions. For this, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…Excessive accumulation of prooxidant substances, such as ROS, can cause oxidative stress in ruminants [ 93 , 94 ]. Some antioxidant enzymes, such as GPx, SOD and CAT are important because they can convert ROS into less harmful compounds for the organism [ 56 ], and consequently can reduce ROS-mediated damage on biological macromolecules [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive accumulation of prooxidant substances, such as ROS, can cause oxidative stress in ruminants [ 93 , 94 ]. Some antioxidant enzymes, such as GPx, SOD and CAT are important because they can convert ROS into less harmful compounds for the organism [ 56 ], and consequently can reduce ROS-mediated damage on biological macromolecules [ 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present meta-analysis, dietary supplementation with TANs increased the activity of antioxidant enzymes (CAT and GPx) and reduced the concentration of malondialdehyde in sheep blood serum. This suggests that inclusion of TANs in the diet could be used as a dietary strategy to mitigate oxidative stress in sheep, which could improve animal health [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Newborn calves have been reported to experience oxidative stress throughout the first month of life [ 10 , 11 ], which has been documented to negatively affect the responsiveness of their immune system [ 12 , 22 ]. This study aimed to investigate to which extent supplementing antioxidants to newborn calves using commercially available micronutrient parenteral supplements improves their redox status and immune response to intranasal vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the immune response elicited by vaccination in newborn calves is lower than in adult cattle [ 5 ]. Newborn calves experience oxidative stress throughout the first months of life [ 9 , 10 , 11 ], which reduces immune cell functions relevant to vaccination responsiveness [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence supports the idea that stress leads to an increase of pro-in ammatory cytokines (N. Li et al, 2016; S. Li et al, 2020). However, the data from animal models and clinical research revealed signi cant variabilities in type I and type II cytokine pro les (Cuervo, Sordillo, & Abuelo, 2021;Koivisto et al, 2019;Razali et al, 2020). It seems to be clear that the examination of a single cytokine, or small groups of cytokines are not su cient to evaluate the alterations of cytokines in depression-related animal models.…”
Section: Effects Of Nai Exposure On Cytokine Levels Of Cms-treated Micementioning
confidence: 93%